2010
DOI: 10.1002/ejoc.201000018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Hindered Polyenynes

Abstract: Keywords: Alkynes / Polyene/polyyne hybrid compounds / Carbon-rich compounds / ThiophenesThe terminal enynes 10-12 were prepared from the corresponding aldehydes 6-8 by applying conventional methods of acetylene chemistry. After exploratory study of the reactivity of these hydrocarbons (preparation of 13, 18, and 19 from 10) these building blocks were subsequently oxidatively dimerized (Glaser coupling) to the sterically protected oligo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Reactions of polyynes higher than butadiynes with sodium sulfide are rare and usually mixtures of different products are obtained. 32 Emission Spectroscopy. Some of the presented thiophenes exhibit strong photoluminescence upon the UV irradiation, thus we recorded absorption and emission/ excitation spectra for all the new thiophenes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions of polyynes higher than butadiynes with sodium sulfide are rare and usually mixtures of different products are obtained. 32 Emission Spectroscopy. Some of the presented thiophenes exhibit strong photoluminescence upon the UV irradiation, thus we recorded absorption and emission/ excitation spectra for all the new thiophenes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our work is the first synthesis of thiophenes from polyyneamines and may be considered as a complementary addition to Witulski’s results and is the first synthesis of 2-amino-5-phenylthiophenes and 2-amino-5-phenylethynylthiophenes from butadiynes and hexatriynes. Reactions of polyynes higher than butadiynes with sodium sulfide are rare and usually mixtures of different products are obtained …”
Section: Results and Discussionmentioning
confidence: 99%
“…Double reaction for octatetraynes is also possible. [80] Very recently we have reported regioselective transformation of surprisingly stable amine endcapped polyynes into substituted thiophenes 134-142. [79] However, octatetraynes not always give selectively one product.…”
Section: Formation Of Heterocyclesmentioning
confidence: 99%
“…It was reported that the reaction of organic octatetrayne 130 with Na 2 S was not regioselective and led to a mixture of different thiophene and bithiophene species (131)(132)(133). [80] Very recently we have reported regioselective transformation of surprisingly stable amine endcapped polyynes into substituted thiophenes 134-142. [81] In this reaction, two triple bonds directly attached to nitrogen are selectively transformed into thiophene ring.…”
Section: Formation Of Heterocyclesmentioning
confidence: 99%
“…Despite the synthetic inaccessibility of longer analogues, hexatriynyl- and octatetraynyl-substituted pyrroles were investigated with the use of computational methods . Moreover, such heterocyclic-long conjugated systems may be used as very useful substrates for the synthesis of oligoheterocycles …”
Section: Introductionmentioning
confidence: 99%